Structural and optical properties in near infrared of CdTeSe coloidal quantum dots for potential application in solar cells - Thang, Pham Nam; Hung, Le Xuan; Minh Chau, Nguyen Thi; Hanh, Vu Thi Hong; Hai, Nguyen Ngoc; Thuc Hien, Nguyen Thi; Nga, Pham Thu (Vietnam Journal of Science and Technology, 2017)
Abstract: This report presents the results on the optical properties of CdTeSe ternary alloyed quantum dots (QDs) fabricated by colloidal chemical method. We have used the micro-Raman spectra as a tool to determine the formation of CdTeSe alloy phase, the composition ratio of Te:Se when fabricated at different temperatures from 180 oC to 280 oC. The intensity ratio of two vibration lines at 159 cm-1 and 188 cm-1 allows the determination of Te:Se composition ratio available in QD samples. The Raman spectra of CdTexSe1-x when x changes between 0, 0.2, 0.4, 0.5, 0.6, 0.8 and 1, fabricated at 260 oC, shows clearly the change in intensity of the optical vibration lines. The  absorption and emission spectra of CdTeSe QDs show that the absorption edge of these QDs shifts up to 880 nm and up to ~ 860 nm for the emission. Detailed studies on size, structural, vibration and optical characteristics of ternary alloyed QDs are also discussed. The absorption region of fabricated CdTeSe QDs are completely suitable for usage in solar cells.